Current challenges to research on animal-assisted interventions. Issue 3 (3rd July 2017) - Serpell, James; McCune, Sandra; Gee, Nancy; Griffin, James A.
ABSTRACT: Studies of the effects of Animal-Assisted Interventions (AAIs) face a number of theoretical and practical challenges. Proposed theoretical processes for the effects of AAIs include those that address primarily the animal's ability to facilitate human–human social engagement, those that emphasize animals' apparent capacity to trigger social attachments and provide nonhuman social support, those that categorize certain animals as supernormal stimuli, those that advance a biophilia hypothesis that living organisms have an innate ability to attract and hold human attention, and those that promote an integrative biopsychosocial model. Each of these generates potentially testable hypotheses, and the field would benefit from systematic efforts to address their validity. Practical challenges to AAI research include issues of study design and methodology, the heterogeneity of both AAI recipients and the animals participating in these interventions, the welfare of these animals, and the unusual pressure from the public and media to report and publish positive findings. Such challenges need to be carefully considered in designing and implementing future studies in the field.